The Demand Forecast and Equilibrium Analysis of Electricity Consumption-take Jiangsu Province as an Example. (May 2017) - Ying, Chen; Hanyu, Li; Wenchao, Li; Lixin, Tian
Abstract: In the background of national energy administration conduct the research on electricity supply and demand equilibrium analysis, this paper forecast variation trend of Jiangsu province's electricity demand, structure and characteristic, combine the construction scale of planned electricity and external power, make the equilibrium analysis from the last year of twelfth-five to thirteen-five plan period. Results shows that Jiangsu province electricity demand growth slows down since industry structure adjustment, however, due to lack of energy resource, it still exist energy gap, specifically, 2017, 2020 has the gap of 18.9, 152.9, 193 Billion Kw/h. Therefore, to ensure the demand of economic and society development, Jiangsu province need replenish certain electricity, and optimize the layout of electricity supply.